Integrating livestock in the CAADP framework: Policy analysis using a dynamic computable general equilibrium model for Ethiopia - Gelan, Ayele; Engida, Ermias; Caria, A. Stefano; Karugia, Joseph T. (International Food Policy Research Institute, 2012)
This study examines the magnitude of the macro and welfare effects generated by a realistic acceleration in the productivity growth of the Ethiopian livestock sector, as compared to historical trends and to alternative scenarios of productivity expansion in the cereal and cash crop sectors. Results from the dynamic general equilibrium simulations show large aggregate gains from livestock productivity acceleration and effects on poor households’ incomes and consumption that are roughly in line with those obtained under cereal growth. This bears important initial implications for the allocation and prioritization of public investment in agriculture in Ethiopia.